Are the criteria of Welfare Economics satisfactory? - Rodríguez Soto, Jorge A. (2024)
Historically, economics was articulate in a dual manner, as science and practice, the separation between scientific and normative aspects is recent. Even so, it is necessary to make the transition between the two levels of analysis to offer solutions to real problems, leaving the issue of how to do it. Faced with this, welfare economics arises, as an appendix to neoclassical theory, providing a criterion with objectivity pretensions to judge and compare policy choices and social arrangements. The objective of this paper is to unify the theory of welfare economics, its decision criteria, and critics. To do this a profound theoretical and critical revision is carried out, regarding welfare economics and general equilibrium theory. The second part of the paper explains the ideas underlying the theory of welfare economics, showing how the transition between efficiency and optimality is made, to separate the positive and normative aspects of the analysis. In the third part, critical revisions to the criterion of welfare economics are presented, pointing out objections to its theoretical assumptions, claims of objectivity, descriptive reality, and narrowness. Concluding that, despite its limitations, the criterion should not be discarded, especially in a society that organizes a great part of its economic activity through the market as the main economic institution; but it isn’t adequate as a unique final criterion either.